Report of the State Auditor ... - Minnesota.
Vols. for 1970/72- issued in two parts: [pt. 1], Report of the State Auditor; [pt. 2], Appropriation statement by departments and agencies (all funds).
Title varies slightly.
Report year irregular.
Vols. for 1970/72- issued in two parts: [pt. 1], Report of the State Auditor; [pt. 2], Appropriation statement by departments and agencies (all funds).